A green approach to the valorization of kraft lignin for the production of nanocomposite gels to control the release of fertilizer. (24th November 2021) - Lotfy, Vivian F.; Basta, Altaf H.
Abstract: The valorization of industrial by‐products is a green approach. This work investigates the valorization of kraft liquor from paper pulping as a precursor in the production of lignin‐based nanocomposites to control the release of monoammonium phosphate (MAP) fertilizer. These nanocomposites were prepared from the stoichiometry of lignin nanoparticles (LNPs) and chitosan (Cs). The lignin nanoparticles were synthesized by solvent exchange and dialysis using two polar solvents: tetrahydrofuran (THF) and ethylene glycol (EG). These LNPs were characterized by transmission electron microscopy (TEM), X‐ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and textural techniques. The TEM images showed that the shapes of LNPs based on THF (LNPT) and LNPs based on EG (LNPE) were spherical, with an average particle size of 300 ± 40 nm and 23 ± 6.5 nm, respectively. Textural characteristics and FTIR revealed no change in the chemical nature of the two synthesized LNPs, and their Brunauer, Emmett and Teller (BET) surface area and average pore diameter ranged from 0.78 to 1.58 m 2  g −1, and 4.069 to 5.20 nm, respectively. Swelling, functional groups, and the thermal, morphology, and MAP release characteristics were investigated for unloaded and loaded chitosan‐LNP nanocomposites (Cs‐LNPs). The water‐swelling capacity of the nanocomposite gel was about 200%. The data indicated that the Cs‐LNP gels can be used as controlled release systems for releasing MAP fertilizer, with maximum releasing value observed for chitosan‐LNPT gel (65%). The kinetic of MAP release from the investigated nanocomposites was followed by the Ritger‐Peppas model with Fickian and quasi‐Fickian diffusion mechanisms. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd